2021
DOI: 10.3389/fpubh.2020.620222
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Evaluation of Serological Assays for the Diagnosis of SARS-CoV-2 Infection and COVID-19

Abstract: Introduction: Few data on the diagnostic performance of serological tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are currently available. We evaluated sensitivity and specificity of five different widely used commercial serological assays for the detection of SARS-CoV-2–specific IgG, IgM, and IgA antibodies using reverse transcriptase-PCR assay in nasopharyngeal swab as reference standard test.Methods: A total of 337 plasma samples collected in the period April–June 2020 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
2
16
0
4
Order By: Relevance
“…However, five RDT products explicitly prescribed to consider any shade of color as a positive reading. In addition, low intensity has been reported frequently among true-positive test lines in COVID-19 RDTs assessed in independent evaluation studies or deployed in seroprevalence studies in Europe [ 14 , 54 , 55 , 56 , 57 , 58 , 59 ]; in the latter studies, proportions of low intensity were comparable to the present cross-reactive line intensities [ 58 , 59 ]. In the case of seroprevalence studies, this may partly be explained by lower antibody levels in non-symptomatic individuals [ 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, five RDT products explicitly prescribed to consider any shade of color as a positive reading. In addition, low intensity has been reported frequently among true-positive test lines in COVID-19 RDTs assessed in independent evaluation studies or deployed in seroprevalence studies in Europe [ 14 , 54 , 55 , 56 , 57 , 58 , 59 ]; in the latter studies, proportions of low intensity were comparable to the present cross-reactive line intensities [ 58 , 59 ]. In the case of seroprevalence studies, this may partly be explained by lower antibody levels in non-symptomatic individuals [ 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…We identified 108 individuals who tested positive for anti-SARS-CoV-2 IgG by an indirect chemiluminescence immunoassay (iFlash CLIA, YHLO Biotechnology, China; specificity 99.3% (98.3–99.7), sensitivity 94% (89.0–96.8)) 92 , 93 , among whom 94 individuals agreed to participate in the follow-up study. Among these, positive anti-SARS-CoV-2 IgG testing was confirmed in 89 participants by at least two further commercial assay systems, and in one further assay system in two individuals, for which material was limited, resulting in a combined specificity of at least 99.94%.…”
Section: Methodsmentioning
confidence: 99%
“…Because the consequences of infection with SARS-CoV-2 range from asymptomatic to lethal, accurate confirmation of previous infections is of great epidemiological and prognostic significance. Serological testing has made great advances (Chiereghin et al, 2020;Galipeau et al, 2020;Huang et al, 2020;Zarletti et al, 2020), but the specific IgG response wanes over time, and some donors with previous infections score negative in current serology tests (Abayasingam et al, 2021;Dan et al, 2021). We showed that the donors who lost IgG to SARS-CoV-2 still had specific IgG memory B cells.…”
Section: Discussionmentioning
confidence: 77%